1995
DOI: 10.1021/bi00009a025
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of minor groove ligands to an AAATT/AATTT site: correlation of thermodynamic characterization and solution structure

Abstract: A combination of circular dichroism spectroscopy, titration calorimetry, and optical melting has been used to investigate the association of the minor groove ligands netropsin and distamycin to the central A3T2 binding site of the DNA duplex d(CGCAAATTGGC).d(GCCAATTTGCG). For the complex with netropsin at 20 degrees C, a ligand/duplex stoichiometry of 1:1 was obtained with Kb approximately 4.3 x 10(7) M-1, delta Hb approximately -7.5 kcal mol-1, delta Sb approximately 9.3 cal K-1 mol-1, and delta Cp approximat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
95
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(108 citation statements)
references
References 23 publications
(48 reference statements)
13
95
0
Order By: Relevance
“…Such behavior is somewhat surprising since the 5 0 -AAAAA-3 0 sites, when unoccupied, are known to accommodate only one DST molecule and only after such 1 : 1 binding is completed the accommodation of the second DST molecule can take place. 33,34 Moreover, binding affinity of a single DST molecule for the 5 0 -AAAAA-3 0 site is significantly lower than the corresponding affinity of a single NET molecule (Table 1). 43 Our results suggest that NET molecules bound to the 5 0 -AAAAA-3 0 sites locally widen their minor grooves to such extent that upon titrating with DST the high affinity 2 : 1 binding of DST that prevails over the 1 : 1 binding of NET becomes possible.…”
Section: Diversity Of Dst and Net Binding Patternsmentioning
confidence: 95%
See 1 more Smart Citation
“…Such behavior is somewhat surprising since the 5 0 -AAAAA-3 0 sites, when unoccupied, are known to accommodate only one DST molecule and only after such 1 : 1 binding is completed the accommodation of the second DST molecule can take place. 33,34 Moreover, binding affinity of a single DST molecule for the 5 0 -AAAAA-3 0 site is significantly lower than the corresponding affinity of a single NET molecule (Table 1). 43 Our results suggest that NET molecules bound to the 5 0 -AAAAA-3 0 sites locally widen their minor grooves to such extent that upon titrating with DST the high affinity 2 : 1 binding of DST that prevails over the 1 : 1 binding of NET becomes possible.…”
Section: Diversity Of Dst and Net Binding Patternsmentioning
confidence: 95%
“…[27][28][29][30] As shown recently, some of the sites that contain five successive AT base-pairs or one GC and four AT base-pairs can accommodate simultaneously two DST molecules. [31][32][33][34][35] In such 2 : 1 complexes the bound DST molecules are stacked in a head to tail orientation with the charged groups located at the opposite ends of the complex. By contrast, dicationic NET cannot form this kind of a side-by-side arrangement due to the electrostatic repulsion between its charged ends.…”
Section: Introductionmentioning
confidence: 99%
“…The model hairpin DNA used in the previous study was a 20-mer having an (A 2 T 2 ) 2 netropsin binding site and a complete sequence of 5′-d(CGAATTCGTCTCCGAATTCG)-3′. Calorimetric titration experiments performed previously using netropsin and other minor groove binding ligands have shown similar complexity in the enthalpy data indicative of more than one binding process in play [24,[42][43][44]. To date, no one has offered an explanation for the presence of multiple binding processes in the 1:1 interaction of minor groove binding ligands to -AT-rich sequences in DNA.…”
Section: Introductionmentioning
confidence: 99%
“…The changes in the T m values for COTAR2 and COTAR3 are similar to what would be observed bound species, such as Co(III), to a DNA oligomer alters the enthalpic contribution to the duplex stabilfor intrastrand and interstrand cross-linking by cisity. 40 The alteration may, for example, lead to stabiplatin, respectively. 41 It has been demonstrated that lization arising from the resultant favorable electrocisplatin preferentially cross-links DNA in an intrastatic interaction or destabilization arising from hestrand fashion at GG sites and, to a lesser extent, lix distortion at the point of coordination.…”
Section: Resultsmentioning
confidence: 99%